Working for the devil - Saintcrow, Lilith (Orbit, 2007)
In the future, necromance Danny Valentine is hired by Lucifer to track and kill fugitive demon Vardimal Santino and retrieve a relic he stole from Hell. She is given a demon to aid and protect her.